A comparison between the effects of coconut oil and other vegetable oils on human health, with emphasis on heart disease - Azeez, Shamina; Vellamoor, Rajagopal; Jayarama Pai, T.; Vadivel, Arunachalam (Journal of Plantation Crops, 2012)
Medical records of 550 subjects (394 men and 156 women), from an age group of 18-83 years were collated using a standard proforma exploring personal details, their habits, dietary pattern including the dietary oils used such as coconut oil, gingelly oil, sunflower oil and groundnut oil, physiological and clinical status, blood biochemical profile, medications, socio-psychological status, etc. Biochemical data of blood samples were related to the type and quantity of oil consumed. Gingelly oil correlated well with low serum cholesterol levels, followed by sunflower oil, coconut oil and groundnut oil. Irrespective of the type of oil used, quantity of oil consumed played a major role in the serum cholesterol, HDL and triglyceride levels directly. However, all the four vegetable oils studied, appeared safe for human health. This study also challenges the belief that coconut oil is hypercholesteremic in nature.